2011
DOI: 10.4041/kjod.2011.41.6.431
|View full text |Cite
|
Sign up to set email alerts
|

Cone-beam computed tomography assessment of mandibular asymmetry in unilateral cleft lip and palate patients

Abstract: Objective: To determine whether there is any difference between the cleft and non-cleft sides of the mandible in unilateral cleft lip and palate (UCLP) patients, or the right and left sides in control patients; and to determine if there is any difference between the mandibular asymmetry of UCLP patients and that of control patients. Methods: We examined cone-beam computed tomography (CBCT) scans of 15 patients with UCLP and 15 age-and gender-matched control patients. We evaluated 8 linear, 3 surface, and 3 vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 20 publications
3
17
0
Order By: Relevance
“…4,7,25,26 In addition, CBCT technology made it feasible to achieve true (1:1 size) images without magnification and showed high intraobserver and interobserver reproducibilities. 4,7,[26][27][28][29][30][31] In our study, the ICC values for all variables were above 0.913, confirming high reliability. The previous studies investigating the craniofacial morphology of BCLP patients with conventional cephalometric lateral films showed that they have a significantly more retrusive maxilla and mandible, a shorter mandibular length, and greater vertical dimensions.…”
Section: Discussionsupporting
confidence: 83%
“…4,7,25,26 In addition, CBCT technology made it feasible to achieve true (1:1 size) images without magnification and showed high intraobserver and interobserver reproducibilities. 4,7,[26][27][28][29][30][31] In our study, the ICC values for all variables were above 0.913, confirming high reliability. The previous studies investigating the craniofacial morphology of BCLP patients with conventional cephalometric lateral films showed that they have a significantly more retrusive maxilla and mandible, a shorter mandibular length, and greater vertical dimensions.…”
Section: Discussionsupporting
confidence: 83%
“…Most of the linear and volumetric parameters were smaller on the cleft side than on the non-cleft side, although only the mandibular-body length and FRI differences were statistically significant. Veli et al9 examined the mandibles of UCLP individuals using cone-beam CT and reported mandibular symmetry, with the exception of the coronoid unit length. We attribute the differences between this result and our results to the use of different research methods and subjects: their study excluded subjects with chin deviation > 2 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Kurt et al7 reported no statistically significant differences in condylar length or ramal length between the cleft and non-cleft sides; in addition, Son and Kim8 measured the ramal length and mandibular-body length on PA radiographs and found no differences in mandibular morphology between the cleft and non-cleft sides. Recently, Veli et al9 studied CBCT images of UCLP patients and reported symmetrical mandibles.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies comparing images from the same individuals have shown that measurements from 2D cephalograms are often not as accurate as those from 3D CBCT images because anatomical features are obscured in cephalograms and a loss of dimensionality occurs when 3D structures are reduced to 2D images (Kula III et al, ). In another investigation dedicated to the analysis of the mandible of persons with non‐syndromic UCLP, researchers studied 3D CBCT images of individuals ranging from 17 to 25 years of age and discovered significant side‐to‐side differences in measurements from the superior coronoid process and the fossa of the mandibular foramen on the clefted side of the face and significantly lower mandibular body volume in the non‐syndromic UCLP group compared with age‐ and gender‐matched controls (Veli et al, ). Interestingly, others determined that patients with non‐syndromic UCLP, ranging from 15 to 20 years of age, have significant upper facial, midfacial, and lower‐facial asymmetry, including several measurements from the mandible (Patel et al, ); results which correspond well to those presented in the current investigation.…”
Section: Discussionmentioning
confidence: 99%